Pengembangan Sistem Internet of Things (IoT) Untuk Monitoring Parameter dan Penggunaan Energi Listrik Satu Fasa Berbasis Web Terintegrasi Pada N8N - Arif Tri Widiyatmoko; Hizbullah Ridwan (DPPM Universitas Pelita Bangsa, 2025)
This study aims to design and implement a web-based Internet of Things (IoT) system for real-time monitoring of single-phase electrical parameters and energy consumption. The system utilizes an ESP32 microcontroller and a PZEM-004T sensor to measure voltage, current, power, frequency, energy consumption, and power factor, with data displayed on a web dashboard. Integration with the n8n platform enables automatic Telegram notifications when electrical parameters exceed predefined thresholds. Testing results indicate that the system provides accurate measurements with an average error below 5%, in accordance with IEC 13B-23 standards, and effectively detects abnormal electrical conditions. The implementation of this system facilitates efficient monitoring and recording of electrical energy usage, while supporting energy efficiency efforts and preventing potential equipment damage.